The Effectiveness Implementation of Package Payment System (INA-CBGs) at Inpatient Installation of RSUD Zainoel Abidin Banda Aceh - Herianti Herianti; Said Usman; Irwan Saputra; Safrizal Rahman; Marthonies Marthonies (Budapest International Research and Critics University, 2020)
Regional General Hospital Dr. Zainoel Abidin (RSUDZA) is one of the public service installations that provide direct health services to the community, especially outpatient and inpatient services. RSUD dr. Zainoel Abidin has implemented a package payment system (INA-CBGs) since January 2014. One of the management elements of implementing this system is planning. Planning (planning) is a process that is very important of all other management functions, which specifically includes the actions to be carried out in order to achieve goals. This study uses a mixed method that uses a combination of descriptive quantitative research and qualitative research with a phenomenological approach through in-depth interviews with informants (in-depth interview). The data used to assess the effectiveness of implementing package payment systems (INA-CBGs) is secondary data taken from hospital medical records. The statistical results assess the frequency distribution by comparing the effectiveness before and after the implementation of the package payment system (INA-CBGs) at RSUD dr. Zainoel Abidin Banda Aceh. The results showed the INA-CBG system was more effective than the Fee for Service (FFS) payment system. The results of this study indicate an increase in efficiency based on service indicators before / after the application of the INA-CBG system, namely (BOR: 75% / 72%, AvLOS: 5 days / 4 days, TOI: 2 days / 1 day, BTO: 46 times / 58 times, GDR: 6 per 1000 patients with discharge / 27 per 1000 patients with discharge, and NDR: 8 per 1000/21 per 1000). It can be concluded that the planning process (planning) of the implementation of the package payment system (INA-CBGs) which has been implemented well by the RSUD Dr. Zainoel Abidin Banda Aceh, including the provision of adequate Human Resources (HR), provision of adequate facilities (infrastructure and facilities), the process of formulating and forming strategies and the process of preparing the budget. The implication of implementing this system has been to be able to increase the efficiency of hospital service performance.